Hubungan Usia dan Jenis Kelamin terhadap Kadar Kolesterol - Muhammad Arif; Mario Sandro (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Cholesterol sufferers in Indonesia are quite high, reaching 28%. If treated too late, high cholesterol will endanger health, and can even cause death. Risk factors that influence cholesterol levels are age, gender, BMI, and blood pressure. Carrying out screening through routine cholesterol level checks is important for early detection and prevention of heart and blood vessel disease caused by increased cholesterol levels. This research method uses a cross-sectional study research design. The number of samples in this study was 20 respondents. Sampling in this study used a purposive sampling method. Data analysis used the Chi Square test. The results showed that there was no relationship between cholesterol levels and age and gender (p-value=0.343) (p-value=0.391)